Publishing Chinese art: issues of cultural reproduction in China, 1905-1918 - Liu, Y (2011)
This thesis is an enquiry into the conditions in which various understandings of the newly introduced but vaguely grasped Western notion of ‘art’ emerged and sustained themselves in the name of cultural reproduction in early twentieth-century China. This Western concept of art was translated into Chinese as ‘meishu’, a neologism originally coined in Japanese kanji, and regarded as the embodiment of the ‘national essence’. Through a close examination of five art-related publishing events—the publication of the nationalistic journal Guocui xuebao; the launch of the art periodical Shenzhou guoguangji; the endeavours to compile a book collection on art, Meishu congshu; the making of the text Zhonguo yishujia zhenglüe which claimed to be a history book of Chinese ‘meishu’; and an example of image appropriation from Stephen Bushell’s Chinese Art—this thesis explores the ways in which different ‘neologistic imaginations’ of the term ‘meishu’ were constructed through publishing practices attempting to preserve and reproduce the ‘national essence’, by creating from the existent tradition a category of ‘art’ equivalent to that in the European West. Unlike previous scholarship, which deems any understanding of ‘meishu’ that deviated from the ‘authentic’ European model a ‘misconception’, this thesis sees these disparate understandings of ‘meishu’ as equally valid statements competing for dominance in the discursive field of art. This thesis thus argues that there existed at least three modes of utterances regarding the notion of ‘meishu’ in early twentieth-century China, and that the success of any such given utterance depended upon the acceptance of the authentic quality argued in its strategy of cultural reproduction. This thesis hence not only offers a detailed analysis of each publishing event, but also provides an interpretative framework within which the recognition of these utterances can be analysed by their strategic approaches to claiming cultural authenticity.